All-solution processed CuGaS2-based photoelectrodes for CO2 reduction - Brito, Juliana Ferreira de; Andrade, Marcos Antonio Santana; Zanoni, Maria Valnice Boldrin [UNESP]; Mascaro, Lucia Helena (Elsevier, 2022)
Considering the influence of carbon dioxide (CO2) on global warming, an all-solution approach is presented here to fabricate nanocrystalline film of the ternary chalcopyrite for the photoelectrochemical CO2 reduction. High-purity nanocrystalline catalysts CuGaS2, Cu(Ga,Bi)S2, and Cu(Ga,In)S2 were obtained by a facile and fast spray method using a molecular ink. Those semiconductors were evaluated in the photoelectrocatalytic CO2 reduction under illumination of 1 Sun (100 mW cm−2) applying potentials from − 0.3 V to − 0.7 V vs Ag/AgCl. Methanol was identified as the major product, furthermore, 2 C and 3 C compounds were also identified. Despite the interesting results, doping with In and Bi caused the formation of defects in the absorber layer, probably inducing recombination mechanisms, thus, affecting the stability and the performance of the photocathode in the CO2 reduction. Meanwhile, Mo/CuGaS2/CdS/TiO2 photocathode showed promising stability and reproducibility for CO2 reduction under illumination (100 mW cm−2) for 240 min at − 0.7 V.
Keywords: Carbon dioxide; Chalcopyrite; Methanol; Photoelectrocatalysis; Solution-processed